Da'wah Policy Controversy: A Case Study of Discourse on Standardization and Certification of Da'i in Indonesia - Umdatul Hasanah; Nur Asia Tawang (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2022)
This paper aims to analyze the controversy regarding the discourse of standardization and certification of da'i in Indonesia to increase the competence and qualifications of da'i. The research was conducted through a qualitative approach with data sourced from observations and documentation of media texts in the mass media and information from interviews. The study results show that differences in authority, interests, ideology and the da'wah market have become forces that structure different views and meanings on the discourse of the standardization and certification of preacher's programs. Differences in meaning have consequences for the occurrence of tug-of-war and other patterns in the standardization and accreditation of preachers in Indonesia. The differences in authority, interests, and ideologies in the component of authority holders have become critical differentiating factors in interpreting a da'wah reality. The research implies that besides providing academic contributions, it also obtains data which is the basis for controversy, giving birth to an understanding that is mutual respect, not suspicion. This paper has limitations regarding methodology, the number of informants and approaches. For this reason, this study suggests the need for segment expansion and a more varied approach to show a more comprehensive understanding in subsequent research.